Rossetti, L. (2017). Another Parmenides (vol. 1-2). Diogene Multimedia - Sánchez-Castro, Liliana Carolina (Estudios de Filosofía, 2021)
Parmenides of Elea is one of the pre-Socratic thinkers who has had (and continues to have) the greatest impact on the philosophical tradition. In fact, the reception that Parmenides has among logicians, metaphysicians and philosophers of language is easily verifiable. Since Antiquity itself, Parmenides enjoyed such popularity to the point that his name has been indelibly associated with the term “being.” However, in philosophical traditions, just as there are winners and losers, and it is normally the first who occupy the places of prestige in the traditions. Likewise, there are facets of a thinker that are privileged and remain associated with a certain name, obscuring any hint of prominence that the others may have. That is also the case with Parmenides. Having been so successful in being associated with a theory of being also resulted in all of Parmenides’ other interests, and with them all the investigative paths that his thought could open, being completely ignored.